Prevalence of Anxiety, Stress, Depression among Malaysian Adults during COVID-19 Pandemic Movement Control Order - Perveen, Asma; Hamzah, Hazalizah; Othamn, Azizah; Ramlee, Fatanah (Indian Journal of Community Health, 2020)
Background: The COVID- 19 virus is not only effecting physical health, but immensely effecting on psychological health. Objective: To evaluate the psychological health issues, stress, anxiety and depression, among the adult population during the movement control period of COVID-19. Design: Research study is cross-section design, online data collection through social media and internet. Methods and Material: Online cross-sectional survey was conduct (n=716) using Depression, Anxiety and Stress scale (DASS). Statistical analysis used: descriptive statistical analyses, to highlight the prevalence rate of psychological issues and coping response using SPSS. Results: The prevalence in score of Stress 70% (Mean=2.02), Anxiety 67% (Mean=1.71) and Depression 42.3% (Mean=2.28). Conclusions: There is significant prevalence of psychological health issues among adults during the adverse unavoidable circumstance due to COVID-19 Pandemic movement control order.